Building London’s Food Democracy: Assessing the Contributions of Urban Agriculture to Local Food Decision-Making - Hasson, Alban (2019)
This article presents the contributions of Urban Agriculture practitioners in establishing the local food movement and the foundations of an active food democracy in London. It argues that food democracy is emerging from a set of contestations within institutional channels, but also through the historical struggle of formulating the dominating political discourses, both of which are co-constituted through specific social and political practices. Webster and Engberg-Pedersen’s political space framework (2002) breaks up this article in order to describe: 1) How specific institutional channels form different strategies of collaboration and contestation; 2) how these are reflected in political discourses evolution; and 3) what dilemmas and opportunities this evolution in practice entails in relation to responsibilisation and its influence on the possibility of establishing true active food democracy in London.